6th UiTM basic laparoscopic skills workshop (BLSW) 2022 - Abdul Manap, Shaiful Amir (Faculty of Medicine, 2022)
The Department of Surgery, HUiTM, had successfully organized the 6th UiTM BLSW 2022 on 23rd and 24th March 2022. This event was officiated by the Deputy Director of UiTM Hospital (HUiTM), Assoc Prof Dr. Ahmad izzuanuddin. Apart from the UiTM' s surgeons, few experienced surgeons in the country were invited to make this workshop successful . Among them was Assoc. Prof Dato Dr. Nik Ritza Kosai, a renowned Upper G. iSurgeon, and Dr. Zairul Azwan, Col orectal Surgeon from PPUKM. Senior Consul tant Surgeon from ipoh Hospital , Dr. Yan Yang Wai, was also present. The program was attended by 18 participants, including master' s students in generalsurgery and senior medicalofficers from Malaysia.